A ROLE OF COMPUTER SIMULATION IN ACCOUNTING EDUCATION. - Sprouls, R. Clay (The Accounting Review, 1962)
This article reports on a seminar, which was conducted to figure out the role of computer simulation in accounting education. Some schools of accounting do teach accounting systems and require that their students study them. For them, the computer simulation is not an introduction to systems but a laboratory for the systems course. It may be used to test out a system or changes in a system as these are studied in the course. Further, if, as so often happens, the systems course should be so broad and general that it contains little or no detail, the computer simulation will force both instructor and students to pay attention to the grubby details so necessary to implement the system, for the simulation with its ultimate computer programming demands that these details be present and accounted for. In either case, the use of a computer simulation of the business that should not be overlooked as a powerful potential new method in accounting education. An educational experience quite different from playing a management game or operating a firm was developed during a recent seminar on business simulation as students actually designed some of the models which comprise the firm.